Ethnomathematical concepts in the slametan tradition for mathematics learning in elementary schools - Oktaviani Adhi Suciptaningsih; Tommy Tanu Wijaya; Andri Setiyawan; Syifa Zia Muharni (Universitas Papua, 2026)
Mathematics learning in elementary schools is often presented abstractly and remains disconnected from students’ socio-cultural experiences. This study aimed to explore ethnomathematical concepts embedded in the slametan tradition of Central Javanese communities and analyze their potential as a resource for culturally responsive mathematics learning. A qualitative ethnographic approach was employed in Sukorejo Village, Kendal Regency, involving 150 community members. Data were collected from April 2025 to May 2026 through observations of six slametan events, semi-structured interviews, open- and closed-ended questionnaires, and documentation. The data were analyzed through data reduction, domain analysis, taxonomic analysis, ethnomathematical interpretation, and data presentation, while trustworthiness was strengthened through triangulation and member checking. The findings revealed that slametan incorporates concepts of numbers and arithmetic operations, fractions, ratios, measurement, estimation, geometry, patterns, symmetry, spatial arrangement, classification, time, and simple statistics. These concepts emerge in determining participant numbers, calculating food requirements, distributing berkat, measuring ingredients, arranging dishes, and organizing space and time. These mathematical practices are also intertwined with Javanese values of rukun, mutual cooperation, tepa salira, gratitude, fairness, and harmony. Therefore, slametan offers an authentic context for meaningful, contextual, and culturally responsive mathematics learning.